ANALYSIS OF FACTORS AFFECTING TUNA FISHERMEN'S INCOME IN GALALA VILLAGE, MANDIOLI SELATAN DISTRICT SOUTH HALMAHERA REGENCY - Abudu, Lasandri; Pasongli, Hernita; Safitri, Yuni Andriyani; Aryuni, Vrita Tri (USN Kolaka, 2024)
Capture fisheries are inherently risky considering the resources used are shared, open management, and dependent on weather, seasons, migration patterns, and fish characteristics. This uncertainty can cause income fluctuations both in terms of time and quantity, which have a significant impact on the quality of life of fishing communities, including in the research location. With this background, research related to the analysis of factors that influence the income of tuna fishermen is very important. The method used in this study is descriptive qualitative with a snowball sampling technique totaling 11 people. The data collection instrument uses observation sheets, documentation and open interviews as primary data sources in this study. Based on the results of research conducted by researchers in Galala Village, it was found that in sequence the most influential factors were fishermen's working capital, followed by fuel oil, tuna prices, fishermen's labor, fishermen's work experience on their income. Weather factors, fish prices, tend to fluctuate so that it is difficult to predict the catch that fishermen will get after going to sea. However, other factors can be managed well through investment in operational costs and adequate fishing equipment by the government so that the volume of catch increases.